Cross-sectional study on the drug utilization and evaluation indicator of antibiotics used in pediatric population - Xu Hu; Xueting Zhang; Yao Wang; Xuefeng Xie (BMC, 2021)
Abstract Background The lack of medication standards is a serious problem in paediatrics mainly because of age-related differences in organ development and physiological functions in children. Consequently, dosage measurement becomes inaccurate. For this reason, methods for evaluating and monitoring rational paediatric medications should be developed. Drug use indicators, such as those similar to the drug utilisation index (DUI) based on the Anatomical Therapeutic Chemical/Defined Daily Dose (DDD) and widely used for the assessment of appropriate dosage in adults, should be explored in terms of their applicability to children. Methods A total of 5,538 prescriptions of antibiotics selected from a general teaching hospital were included. Drug, dose, frequency and treatment duration were obtained from each prescription. The prescription daily dose (PDD) of each antibiotic drug was calculated as the average of the daily doses. Underdose and overdose were determined in terms of the PDD/DDD ratio for each prescription. Children's DUI (cDUI) was explored in terms of the appropriate dosage for children as follows: the meaning of children's DDD (cDDD) and the evaluation of paediatric drug dosage. Results The top five antibiotics and their utilisation rates were as follows: cefmetazole sodium injection (18.47 %), erythromycin lactobionate injection (15.07 %), amoxicillin/clavulanate potassium injection (10.72 %), ceftriaxone sodium injection (9.50 %) and azithromycin dry suspension (8.02 %). The ratio of cDUI and PDD/cDDD was mostly not close to 1. Conclusions The establishment of a cDUI system is an effective means of paediatric dosage evaluation. In addition to DDDs, cDUI and PDD/cDDD should be used to analyse the utilisation of antibiotics in children.